Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae) - Tang, Chufei; Zhu, Yajun; Yang, Ding (Zootaxa, 2019)
The Himalayan region now includes 67 species in seven genera of Sciapodinae, including nine new species (Amblypsilopus acuminatus sp. nov., A. liangi sp. nov., A. liratus sp. nov., A. marginatus sp. nov., A. medogensis sp. nov., A. quinquepetalus sp. nov., Plagiozopelma fornicata sp. nov., P. trilobata sp. nov., Sciapus zewoiensus sp. nov.). Six species are reported from the Himalayan region for the first time: A. baoshanus Yang, A. didymus Yang, A. hubeiensis Yang & Yang, A. imitans (Becker), A. liui Zhu & Yang, and P. medivittatum Bickel & Wei. Chrysosoma insensibile Yang is re-assessed and transferred to Amblypsilopus, new combination. Amblypsilopus sinensis Yang & Yang, 2003 is proposed as a new synonym of A. subabruptus Bickel & Wei, 1996. This is the first time Sciapus Zeller is reported from the Himalayan region. Keys to genera and species of Sciapodinae occurring in the Himalayas are provided. The distribution of Sciapodinae in the Himalayas is discussed.